CYTOTOXIC ACTIVITY OF SELECTED LIBYAN MEDICINAL PLANTS ON HUMAN BREAST ADENOCARCINOMA CELL LINE (MCF-7) - Jamal, Elmezogi; Gazala, Ben Hussien; Mabrouk, Erhuma; Manal, Gadmour; Abdulmotaleb, Zetrini; Abossa, Abdolgader; Shilpi, Jamil Ahmad (Indonesian Journal of Pharmacy, 2013)
Three Libyan plants namely Ballota pseudodictamnus, Hedera helix, Thapsia garganica were tested for anticancer activity. The plants, collected from Aljabal-Al-Akhdar area of Libya in April 2010 were shed dried and subjected to Soxhlet extraction by methanol. Phytochemical screening indicated the presence of 2-deoxy sugars, flavonoids, saponins and tannins but absence of alkaloids in all three plants under investigation. Antiproliferative activity was performed breast adenocarcinoma cell line (MCF7). At the concentration of 100µg/mL, B. pseudodictamnus, T. garganica and H. helix showed 90, 60 and 5% cell death, respectively as compared to the control. Key words: Antiproliferative; Breast adenocarcinoma; Cell l ine MCF-7